Plasmolysis in Bacillus megaterium - Weibull, Claes (J Bacteriol, 1965)
Weibull, Claes (Central Bacteriological Laboratory of Stockholm City, Stockholm, Sweden). Plasmolysis in Bacillus megaterium. J. Bacteriol. 89:1151–1154. 1965.—Sucrose solutions stronger than 1 m caused plasmolysis in Bacillus megaterium strain M, whereas concentrated NaCl and KNO(3) solutions were ineffective. In plasmolyzed cells, mesosome bodies were found in pockets between the cytoplasmic membrane and the cell wall. After plasmolysis, the cytoplasmic membrane appeared as a triple-layered structure, a “unit membrane.” Plasmolysis did not markedly influence the viability of the cells. IMAGES: